Students’ Reading Habit and Their Reading Comprehension in Learning English - Nurhayati; Geraldo Amelius Najoan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to find out the correlation between students’ reading habit in learning English and their reading comprehension in learning English and was used quantitative descriptive approach. The data was collected from 100 students of Grade VII students in SMP Negeri 1 Airmadidi. To answer the research questions, descriptive mean analysis and Pearson Product Coefficient Correlation were used. The findings revealed that the level of students’ reading habit was 3.30, indicating as moderate level. The level of students’ reading comprehension was 2.70, indicating as moderate level, and the p = 0.00, and r = 0.45, indicating that there is a significant correlation between reading habit and reading comprehension. However, the correlation was moderate. Since there is a significant correlation between the two variables, it is important for teachers to pay attention to students’ habit in reading for their good comprehension as well.